ADAPTASI PENGIDAP HIV DAN AIDS SERTA PERAN LSM DI KOTA PEKANBARU - Riadul Jannah; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The number of HIV and AIDS spreading in Pekanbaru city is increasing lately. HIV virus spreading become a social problem when it is caused by individual reasons like free sex, inject drugs, tattoing, and accident in medical world like contaminated blood or organ transfusion. Another problem that should be faced by HIV and AIDS sufferer is the negative stigma and discrimination from society. This situation need to be handled with an adaptation process by the sufferer with the social environment. In this research, writer discuss HIV and AIDS sufferer profile in Pekanbaru city. Writer also discuss the adaptation of the sufferer and NGO’s role in accompanying the sufferer. This is a qualitative descriptive research with purposive sampling technique. There are 5 sufferer as the sample. These 5 sufferer assisted by NGO Sebaya Lancang Kuning. Result shows that adaptation process of HIV and AIDS sufferers is higly influenced by their knowledge about HIV and AIDS. Sufferers will be more easy to adapt if they are supported by family and friends in social environment. In adaptation process, NGO’s role is huge in transferring the knowledge about HIV and giving support for HIV and AIDS sufferer. It is even bigger in sufferer who does not get social suppoert from family and friends.Key word: Adaptation, HIV and AIDS, Social support.